Competing through the last mile: Strategic 3D printing in a city logistics context. (July 2021) - Demir, Emrah; Eyers, Daniel; Huang, Yuan
Highlights: 3D printing from a city logistics perspective is investigated for the first time. An algorithm that enables multi-period production and delivery planning is presented. An empirical case study is provided for a realistic evaluation of the proposed algorithm. Various scenarios on integrated production and delivery are studied. Abstract: Recently, 3D Printing (3DP) has started disrupting transportation worldwide by providing enormous simplifications to transportation requirements, especially in the context of city logistics. In the near future, the potential exists to replace multi-echelon transportation hubs with integrated city logistics and 3D printing manufacturing hubs. This study investigates this integrated concept, particularly for healthcare product distribution (i.e., hearing aids) to customers located within a city environment. We propose an efficient mathematical model to investigate various scenarios of integrated 3DP production and transportation planning and provide insightful analysis. It might seem counter-intuitive that tighter delivery time slots can improve the utilization of capacity and 3DP machines, but this study finds that intelligent selection of production and delivery policies can simultaneously benefit both customer and supplier. By integrating both production and delivery, this study identifies opportunities for firms to survive and thrive in the era of challenging city logistics.